Nutrient Cycling in Eucalyptus globulus Plantation Organic Matter Production, Nutrients Accumulation in Standing Crop and Nutrients Removal through Harvest - George, M.; Varghese, G. (Indian Forester, 1990)
Dry matter production, nutrients accumulation and nutrients removal through harvest in a 10 year old E. globulus plantation was estimated. The total above- ground biomass amounted to 76.877 kg/ha of which 66% was contributed by wood. Root biomass constituted 18% of AGB. On unit area basis 474 kg/ha of N, 32 kg/ha of P and 386 kg/ha of K was accumulated in the total (agb+root) biomass of which 40% to 48% of all nutrients was removed by harvesting wood. The extraction of twigs and bark will cause an additional loss of 9-15% of various nutrients in addition to the loss caused by the removal of leaf which is 7% to 11%. The results emphasise that, necessary safeguards are to be taken to maintain the fertility status of the soils while large area is converted to plantations of E.globulus.